Reduced aggression and foraging efficiency of invasive signal crayfish (Pacifastacus leniusculus) infested with non-native branchiobdellidans (Annelida: Clitellata). Issue 1 (December 2015) - James, J.; Davidson, K.; Richardson, G.; Grimstead, C.; Cable, J.
Abstract Background Biological invasions are a principal threat to global biodiversity and identifying the determinants of non-native species' success is a conservation priority. Through their ability to regulate host populations, parasites are increasingly considered as important in determining the outcome of species' invasions. Here, we present novel evidence that the common crayfish ecto-symbiont, Xironogiton victoriensis (Annelida: Clitellata) can affect the behaviour of a widespread and ecologically important invader, the signal crayfish (Pacifastacus leniusculus ). Methods To assess the signal crayfish–X. victoriensis relationship naïve crayfish were infested with an intensity of worms typically observed under natural conditions. Over a 10-week period the growth rate and survivorship of these animals was monitored and compared to those of uninfested counterparts. Complementary dyadic competition and foraging experiments were run to assess the behaviour of infested compared to uninfested animals. These data were analysed using General Linear Models and Generalized Linear Mixed Models. Results WhilstX. victoriensis did not affect the growth rate or survivorship of signal crayfish under laboratory conditions, infested animals were significantly less aggressive and poorer foragers than uninfested individuals. Conclusions Through reducing aggression and foraging efficiency, infestation withX. victoriensis may disrupt the social structure, and potentially growth rate and/or dispersal of afflicted crayfish populations, with potential effects on their invasion dynamics. This is important given the widespread invasive range of crayfish and their functional roles as ecosystem engineers and keystone species.